Why do Tourist Attractions and Service Quality Mediated by Visitor Satisfaction Influence the Interest in Revisiting Kum-Kum Tourism in Palangka Raya? - Vivy Kristinae; Meitiana Meitiana; Rian Sidiq Prakoso; Citra Sihombing; Ni Luh Wayan Sayang Telagawathi (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the effect of tourist attractions and service quality on revisit intention, with visitor satisfaction as a mediating variable, at Kum Kum Tourism Park, Palangka Raya. The study is motivated by inconsistent findings in previous tourism studies regarding whether tourist attractions directly influence revisit intention and by the managerial need to improve destination sustainability through repeat visitation. A quantitative associative approach was applied using a survey of 100 visitors selected through accidental sampling. Data were collected using structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that tourist attractions and service quality have a positive and significant effect on visitor satisfaction. Visitor satisfaction significantly influences revisit intention. Tourist attractions and service quality also directly and significantly affect revisit intention. Furthermore, visitor satisfaction partially mediates the influence of tourist attractions and service quality on revisit intention. These findings confirm the central role of satisfaction in transforming attraction and service performance into repeat visit behavior. This study contributes to tourism marketing literature by clarifying the inconsistent relationship between tourist attractions and revisit intention through a mediating mechanism. Practically, the findings highlight the importance of improving service quality, facility maintenance, environmental cleanliness, and interactive attractions to enhance visitor satisfaction and strengthen revisit intention at Kum Kum Tourism Park.